Sintering behavior and electrochemical performance of A-site deficient SrxTi0.3Fe0·7O3-δ oxygen electrodes for solid oxide electrochemical cells. Issue 17 (1st September 2021) - Yang, Hao; Hanif, Muhammad Bilal; Zhang, Shan-Lin; Li, Chang-Jiu; Li, Cheng-Xin
Abstract: Sr(Ti0·3 Fe0.7 )O3-δ (STF) materials with satisfactory stability and no rare-metal elements have attracted increasing research interest as oxygen electrodes of solid oxide electrochemical cells. However, STF-based electrodes are still limited by their modest catalytic activities at low temperatures. This can be improved by A-site deficiency of STF-based materials; however, data related to the influence of A-site deficiency of perovskite-oxide-based materials on sintering behavior and electrochemical performance are still lacking. Herein, porous electrodes with different Srx (Ti0·3 Fe0.7 )O3-δ compositions (x = 0.85–1) were prepared. The effects of A-site cation deficiency ratios and sintering temperatures on the microstructures and electrochemical performance of the as-obtained STF electrodes were investigated. Electrochemical performance was improved for A-site deficient Srx (Ti0·3 Fe0.7 )O3-δ . For Sr0·9 (Ti0·3 Fe0.7 )3-δ electrode material sintered at 1050 °C, the lowest polarization resistance measured at 700 °C was ~0.14 Ω⸳cm 2 but increased at higher x values. At sintering temperatures above 1050 °C, the sintering diffusion occurred, where the electrolyte diffused through the deficient electrodes to form a dense layer at the electrode/electrolyte interface. On the other hand, although the presence of such diffused dense layer did not have significant effect on the electrochemical performance of the cells, it could be prevented by using lower sintering temperatures (≤1000 °C) to avoid possible negative effects on comprehensive performance. For the electrode obtained at x = 0.9 and sintered at 1000 °C, the overall polarization resistance was recorded as 0.099 Ω⸳cm 2 at 700 °C. In sum, these findings look promising for future research.